Effects of Ce-Rich Misch Metal on the Microstructures and Tensile Properties of as-Cast Mg-7Al-3Sn-1Zn Alloys - Guo-Jun Liu; Yan-Hua Sun; Nan Xia; Xiao-Fang Guan (Metals, 2021)
The effects of small amounts of Ce-rich misch metal (Mm: 0.5, 1.0 and 2.0 wt.%) addition on the microstructure and tensile properties of as-cast Mg-7Al-3Sn-1Zn wt.% (ATZ731) alloy have been investigated. The addition of Mm restricts the formation of the Mg17Al12 phase but greatly promotes the Al4Mm phase. The proper Mm addition enhances the strength and ductility of ATZ731 alloys at both room temperature (RT) and 175 °C. ATZ731 alloys with 1.0 wt.% Mm addition exhibit an advantageous combination strength and ductility, with the ultimate tensile strength (UTS), 0.2% yield strength (YS) and elongation to failure (Ef) at 175 °C of ~148 MPa, ~102 MPa and ~28%, improved by ~14.7%, ~24.3% and ~53.8%, respectively, compared to those of ATZ731 alloy. This enhancement is primarily owing to the refined microstructures and the high thermal stability of Al4Mm at the elevated temperature in contrast with that of the Mg17Al12 phase. The fracture modes are also discussed.